(untitled) (Research, Society and Development, 2023)
Post-Traumatic Stress Disorder (PTSD) causes several psychological damages to its victims. The objective of the present study was to evaluate the impact of PTSD on the health of children and adolescents, the future consequences that the disorder can cause and the treatments that can alleviate this damage. This research has a qualitative bibliographic approach, using scientific articles published from 2014 to 2022 as a research instrument. A bibliographic survey was carried out in six stages, using the PICO method (population, intervention, comparison and outcome). Articles in Portuguese and English were searched in the Virtual Health Library (BVS), Scientif Electronic Library Online (SciELO), National Library of Medicine (PubMed), Business Source Complete (EbscoHost) and Google Scholar databases. A total of 26 articles were identified, of which 20 met the criteria. It was observed that PTSD causes damage to memory and cognitive functions and can lead to the development of other disorders such as depression and anxiety. The findings of this study also presented some treatment possibilities, such as Cognitive Behavioral Therapy, which is a focal, flexible and short-term treatment modality that presents significant improvements in the symptoms associated with PTSD, being a model, which, in addition to other mentioned during the research, must be developed and applied so that there is the rehabilitation of the affected functions. In this sense, this study contributes to the literature on exposure to psychological violence and its association with the development of Post-Traumatic Stress Disorder, confirming the negative impact of this disorder on the individual’s mental health.